2003
DOI: 10.1038/sj.cgt.7700601
|View full text |Cite
|
Sign up to set email alerts
|

Sustained P450 expression and prodrug activation in bolus cyclophosphamide-treated cultured tumor cells. Impact of prodrug schedule on P450 gene-directed enzyme prodrug therapy

Abstract: Cytochrome P450-based gene therapy can substantially increase the sensitivity of tumor cells to P450-activated cancer chemotherapeutic prodrugs such as cyclophosphamide (CPA) without increasing host toxicity. While the role of 4-OH-CPA, the primary active metabolite of CPA, in eliciting tumor cell death is well established, the effect of 4-OH-CPA exposure on the capacity of P450-expressing tumor cells for continued metabolism and activation of CPA has not been investigated. The present study addresses this que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In this effort, several studies have shown that using retroviral, replicating herpes viral, and adenoviral vectors, regional delivery of CYP2B expression cassette into tumor tissues significantly increased cancer cell cytotoxicity and intracellular 4-OH-CPA formation. 18,19,45,46 Whereas this strategy may benefit patients with localized solid tumors, in the case of hematologic malignancies, systemic treatment is required and bioactivation of CPA primarily relies on hepatic drugmetabolizing enzymes. Our HPH-leukemia cell coculture model represents an excellent in vitro system mimicking human in vivo condition that allows simultaneous investigation of hepatic metabolism and extrahepatic anti-cancer activity under a shared cellular environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this effort, several studies have shown that using retroviral, replicating herpes viral, and adenoviral vectors, regional delivery of CYP2B expression cassette into tumor tissues significantly increased cancer cell cytotoxicity and intracellular 4-OH-CPA formation. 18,19,45,46 Whereas this strategy may benefit patients with localized solid tumors, in the case of hematologic malignancies, systemic treatment is required and bioactivation of CPA primarily relies on hepatic drugmetabolizing enzymes. Our HPH-leukemia cell coculture model represents an excellent in vitro system mimicking human in vivo condition that allows simultaneous investigation of hepatic metabolism and extrahepatic anti-cancer activity under a shared cellular environment.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Although this strategy appears to be attractive in CPA-based treatment of localized solid tumors, it may not be applicable to hematologic malignancies, such as leukemia and lymphoma, in which systemic chemotherapy is necessary. Therefore, drugs affecting hepatic expression of CYP2B6 may profoundly influence the systemic exposure of CPA metabolites, as well as the efficacy and safety of CPA in the treatment of leukemia and lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclophosphamide (CPA) is an example of such a drug. This antineoplastic undergoes N-dechloroethylation to an inactive toxic metabolite exclusively by CYP3A4 and 4-hydroxylation to a therapeutically active metabolite primarily by CYP2B6 (Roy et al, 1999;Schwartz et al, 2003). Assuming that hCAR selectivity for CYP2B6 also occurs in vivo, concurrent administration of CPA with a selective hCAR activator should facilitate enhanced production of its beneficial metabolite without simultaneously increasing formation of its toxic metabolite.…”
Section: Differential Regulation Of Cyp2b6 and Cyp3a4 By Hcar 1207mentioning
confidence: 99%
“…Human CYP2B6 is a clinically important enzyme that metabolizes many commonly used therapeutics and activates anti-cancer pro-drugs, such as cyclophosphamid and ifosfamide (6,7). Two distinct DNA sequences within the CYP2B6 promoter are required for CAR to synergistically activate the promoter activity: the distal phenobarbital-responsive enhancer module (PBREM) and the proximal OA response element now called OARE KI (5,8).…”
mentioning
confidence: 99%